Metode Bimbingan Manasik Haji pada PT. Grand Darussalam - Hafidz, Abdul; Fadli, Fadli; Jasmine, Cinta Aurel; Rahmadhani, Najwa Gusty (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
The Hajj ritual guidance method is a way toResolving problems during the The hajj manasik guidance method is a way to solve problems in the hajj